2011
DOI: 10.1016/j.neures.2011.07.226
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide profiling of the core clock protein BMAL1 targets reveals strict relationship with metabolism

Abstract: 京都大学 博士(医学) 氏 名 畠中 史幸 論文題目 Genome-wide profiling of the core clock protein BMAL1 targets reveals strict relationship with metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
42
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 0 publications
6
42
0
Order By: Relevance
“…Consistent with other published studies (6,7,19), our ChIP-seq results showed that the Gm129 gene has high affinity binding sites for CLOCK, BMAL1, and CRY1 in its promoter region (Fig. 1C).…”
Section: The Gm129 Gene Is a Direct Target Of Clock⅐bmal1⅐cry1supporting
confidence: 93%
See 2 more Smart Citations
“…Consistent with other published studies (6,7,19), our ChIP-seq results showed that the Gm129 gene has high affinity binding sites for CLOCK, BMAL1, and CRY1 in its promoter region (Fig. 1C).…”
Section: The Gm129 Gene Is a Direct Target Of Clock⅐bmal1⅐cry1supporting
confidence: 93%
“…Only one gene remains uncharacterized, gene model 129 (Gm129), which encodes a novel protein with no predicted functional domains. Gm129 is also implicated as a direct CLOCK⅐BMAL1 target gene based upon its strong transcriptional oscillation in liver in a additional independent BMAL1 ChIP-seq analysis using NIH3T3 and WI38 cell lines (6).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…the cistrome) of clock proteins across the circadian cycle. For example, thousands of DNAbinding sites in mouse liver are rhythmically occupied by BMAL1, including genes involved in sterol and TAG metabolic pathways (49,50) . Similarly, the circadian cistromes for REV-ERBα, nuclear receptor corepressor and histone deacetylase 3 overlap extensively and are enriched for genes involved in lipid metabolism (51)(52)(53) .…”
Section: Regulation Of Clock-controlled Genes Involved In Lipid Metabmentioning
confidence: 99%
“…One representative example is the E'-box (CACGTT), which participates in mammalian Per2 gene oscillation [20]. Recently, genome-wide analyses of BMAL1-binding sites by ChIP array or deep sequencing techniques also identified many E-box-like and non-canonical Ebox elements such as CCAATG, CATTGG, CATGTG, AACGTG, which extensively regulate clock-controlled genes [21,22]. These E-boxes can further form tandem repeats to regulate gene expression [22,23].…”
Section: Introductionmentioning
confidence: 99%